2001
DOI: 10.1021/cm000717l
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State 31P/27Al and 31P/23Na TRAPDOR NMR Investigations of the Phosphorus Environments in Sodium Aluminophosphate Glasses

Abstract: Solid-state 31 P/ 27 Al and 31 P/ 23 Na TRAPDOR NMR experiments have been used to investigate the spatial distribution of aluminum and sodium cations with respect to the phosphate backbone for a series of sodium aluminophosphate glasses, xAl 2 O 3 ‚50Na 2 O‚ (50-x)P 2 O 5 (0 e x e 17.5). From the 31 P/ 27 Al and 31 P/ 23 Na TRAPDOR data gathered, information about the medium-range order in these glasses was obtained. The expanded data allow for better identification and interpretation of the new resonances obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
79
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(99 citation statements)
references
References 53 publications
19
79
1
Order By: Relevance
“…Increasing the alumina content of the glass samples leads to a reduction in the amount of six-coordinated aluminium, accompanied by an increase in the fraction of tetrahedrally coordinated aluminium, which constitutes the dominating species at high alumina content. This trend is in good agreement with previous studies of the aluminium speciation in aluminophosphate glasses [6][7][8][9][10]. At low Al 2 O 3 content the phosphate network is mainly formed by Q 1 -species and charge balancing of the aluminophosphate network favors the AlO 6 coordination (as in the KAlP 2 O 7 structure [23]); at higher Al 2 O 3 content, the phosphate network is mainly constituted by isolated orthophosphate species (Q 0 ) and The error on the T g values is estimated to ±10°C.…”
Section: Al-(mq)mas and 31 P-mas Nmrsupporting
confidence: 93%
See 2 more Smart Citations
“…Increasing the alumina content of the glass samples leads to a reduction in the amount of six-coordinated aluminium, accompanied by an increase in the fraction of tetrahedrally coordinated aluminium, which constitutes the dominating species at high alumina content. This trend is in good agreement with previous studies of the aluminium speciation in aluminophosphate glasses [6][7][8][9][10]. At low Al 2 O 3 content the phosphate network is mainly formed by Q 1 -species and charge balancing of the aluminophosphate network favors the AlO 6 coordination (as in the KAlP 2 O 7 structure [23]); at higher Al 2 O 3 content, the phosphate network is mainly constituted by isolated orthophosphate species (Q 0 ) and The error on the T g values is estimated to ±10°C.…”
Section: Al-(mq)mas and 31 P-mas Nmrsupporting
confidence: 93%
“…For the highest Al 2 O 3 contents (glasses KAlP_17.5 and KAlP_20), two resonances at 3 and À6 ppm are observed. This limited spectral resolution, especially in the spectra of the glass samples of medium alumina content, impedes a detailed analysis of the structural changes in the phosphate network upon alumina incorporation based on the 31 P-MAS NMR spectra alone and we have to resort to heteronuclear correlation techniques (as described in [8,9,11]) to increase the spectral resolution. 27 Al}-CP-HETCOR NMR 31 P{ 27 Al}-CP-HETCOR NMR experiments for glass samples KAlP_5, KAlP_7.5, KAlP_10, KAlP_15 and KAlP_20 are compiled in Fig.…”
Section: Al-(mq)mas and 31 P-mas Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of Ca-free sodium aluminophosphate glasses, Zhang and Eckert [53] reported 31 P chemical shifts of ~1.6 and -4.6 ppm, which they also assigned to Q 1 units with 0 and 1 bonded aluminium units respectively, in agreement with the results of Lang et al [54].…”
Section: P Mas and 31 P{ 1 H} Cp/mas Nmrsupporting
confidence: 81%
“…Previous investigation on the solution of aluminum lactate and sodium The 31P spectra ( Figure 2) are composed of four species around 0, -7, -12 and -17 ppm, respectively. We will designate the phosphorus species in aluminophosphate materials using a Qn(mAl) notation [20][21][22], where n is the number of P next-nearest-neghbor (NNN) per P tetrahedron and m is the number of Al NNN per P. Note that this notation makes no distinction as to the species of aluminum. It's readily to assign 0 and -7 ppm to free orthophosphate (i.e.…”
Section: Experimental Procedures Preparation and Methodsmentioning
confidence: 99%